ASC520: Financial Economics I / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course introduces the derivative market products. It emphasizes the importance of the theory, pricing, strategies involve and derivation of formula in business applications.